El General de Brigada Martín Perfecto de Cós, Comandante General é Inspector de los Estados Internos de Oriente : á nombre del Presidente de la República . - Cos, Martín Perfecto de, 1800-1854 ([publisher not identified], 1835)
A warning to Texan settlers who would chose to live by their own laws without respecting those of the Mexican nation.